Scenarios for the Food Industry in 2010 - Hanne Harmsen; Birger B. Jensen; Anne-Mette Sonne (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
While predicting the future is impossible, corporate decision-makers have to decide which competencies to develop precisely on this basis. This article presents the results of a research project on scenario analyses in the Danish food industry. The aim of the study is to look at alternative visions of the future of the food industry and to assess their implications for competence requirements. Given the uncertain nature of the environment, food companies cannot rely on today's competencies being sufficient to fulfil the demands of tomorrow's markets. However, predicting the determinants of success in the food industry 10 years hence is a daunting task. Scenario techniques can be very useful in this respect (VON REIBNITZ, 1988). The contribution of the article is the methodological approach to scenario building, which combines academic and industry input and translates the scenarios into the required competencies in each scenario. From an industry point of view, the competencies identified in each scenario can stimulate discussions of strategic choice in the food sector.
Keywords: 330; Ernährungsindustrie; Erfolgsfaktor; Kompetenz; Szenariotechnik; Dänemark